2021
DOI: 10.1016/j.onehlt.2021.100357
|View full text |Cite
|
Sign up to set email alerts
|

PADI-web 3.0: A new framework for extracting and disseminating fine-grained information from the news for animal disease surveillance

Abstract: PADI-web (Platform for Automated extraction of animal Disease Information from the web) is a biosurveillance system dedicated to monitoring online news sources for the detection of emerging animal infectious diseases. PADI-web has collected more than 380,000 news articles since 2016. Compared to other existing biosurveillance tools, PADI-web focuses specifically on animal health and has a fully automated pipeline based on machine-learning methods. This paper presents the new functionalities of PADI-web based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…with Natural Language Processing (NLP) approaches. In 13 we summarized how the corpus described in this study is used to learn a fine-grained classification model based on a machine learning approach that is integrated into PADI-web 3.0. The proposed annotation scheme is intended to enhance EBS systems by enabling the automated classification of sentences from disease-related news.…”
Section: Methodsmentioning
confidence: 99%
“…with Natural Language Processing (NLP) approaches. In 13 we summarized how the corpus described in this study is used to learn a fine-grained classification model based on a machine learning approach that is integrated into PADI-web 3.0. The proposed annotation scheme is intended to enhance EBS systems by enabling the automated classification of sentences from disease-related news.…”
Section: Methodsmentioning
confidence: 99%
“…The uptake of EI systems, such as EIOS, was far from being generalised across all infectious diseases models. The generalisation of EI systems might be hampered by their limited performance for ltering noise and irrelevant items and validation of signals and analysis (24)., This requires time-consuming involvement of trained personnel, and leading agencies to favour the use of more trustworthy sources, such as scienti c literature, despite poor timeliness, and mainstream media, despite limited coverage of a range of online sources. For several disease models, the capture, ltering and validation of EBS signals were not part of the EI activities, raising concerns about countries capacities to early detect potential health threats, and the need to train PH and AH professionals in collection, analysis and interpretation of EBS signals, either through in-country initiatives, European capacity building, or within the development of the WHO's Pandemic Hub in the coming years (7,25,26).…”
Section: Event-based Activities: Data Sources and Processesmentioning
confidence: 99%
“…Our ndings showed that manual assessment of IBS and EBS signals i.e., expert review, was the main method used, emphasising the demand for continuous availability of trained personnel. The implementation of automatic or semi-automatic methods and tools (19,24,27), including forecasting or the use of data science and arti cial intelligence techniques for rapid processing of EI data could be of interest for better allocation of resources, to decrease the current workload of EI o cers and effectively support government agencies, healthcare service providers, and medical professionals in the future (28, 29).…”
Section: Signal Assessment and Communication Of Alertsmentioning
confidence: 99%
“…The emergence and spread of any animal infectious disease, such as Avian Influenza, has serious consequences for animal health and a substantial socio-economic impact for agriculture. For instance, the 2021-2022 season have experienced the largest observed highly pathogenic avian influenza (HPAI) cases in Europe so far, with a total of 2,467 outbreaks in poultry, 3,573 HPAI events in wild birds, and 48 million birds culled in the affected establishments 2 . Due to this highly contagious nature, it is critical to monitor new and emergent infectious animal diseases.…”
Section: Introductionmentioning
confidence: 99%